Peace and Warfare in the Context of International Law Violations and Global Security - Fatema Miah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Warfare alliances, and UN’s in the War, among the objectives of the UN, the key was the development of friendly and cordial relations among the member countries. To enabling the advancing, for the progress of member countries, and for maintaining the respect, between the parties. However, the serving of international law and its effectiveness in promoting peaceful settlement of disputes remains a pressing concern in the global governance, hence there is absence of Peace globally, and the worlds political sphere is in division in perspective of the Global, International Relations, per to there is USA’s dominant global dictation and power assertion is evidence of there is absence of essential application of epistemological rules’ terms, virtues in the global political international relation sphere.